Transparency of Add-On Fees on Peer-to-Peer Platforms: Evidence from Airbnb - Kevin Ducbao Tran; Leonardo Madio; Michelangelo Rossi; Mark J. Tremblay (CESifo GmbH, 2024)
This paper investigates the impact of price transparency on equilibrium prices and fees by considering a policy change implemented by Airbnb that affected the transparency of cleaning fees for IP addresses from the European Union (EU). Using a difference-in-differences approach, we find a reduction in cleaning fees of 2-4%. Consistent with our theoretical framework, we also find that listings without a cleaning fee, something that is common on Airbnb, appear more affordable after the policy change and react by increasing their nightly price by 5-6%. We argue that this result is driven by some hosts learning about the full prices of their rivals due to the transparency policy, finding themselves more affordable. This analysis uncovers a new mechanism through which greater price transparency can lead to price increases.
Keywords: D40; D80; L10; L20; L40; 330; price transparency; obfuscation; cleaning fees